(untitled) (REMUNOM, 2025)
INTRODUCTION: Cholelithiasis and acute cholecystitis are common medical emergencies worldwide related to the gallbladder. They cause pain in the right upper quadrant (RUQ) of the abdomen, which can radiate to the shoulder or right scapula, and are often associated with vomiting and low-grade fever. Together, these conditions cause a large number of hospitalizations, representing a growing public health problem. OBJECTIVE AND METHODOLOGY: The objective of this study was to describe the impact of cholecystitis and cholelithiasis on the Unified Health System (SUS) using data from 2019 to 2024, to outline the epidemiological profile of the disease in Brazil. The methodology was a descriptive epidemiological study, using hospital morbidity data from the SUS Hospital Information System (SIH/SUS). RESULTS AND DISCUSSION: Brazil had a total of 1,801,474 hospitalizations for these diseases during the period. In 2024, the rate was 188 hospitalizations per 100,000 inhabitants. The concentration of cases was highest among those over 30, with an average of 350,000 cases among those aged 30 to 59. Regarding gender, the disease affected more women, with approximately 1,316 hospitalizations per 100,000 women. Deaths were more common in emergency care, with an average mortality rate of 1.7 deaths during the period. The average cost per hospitalization was R1,090.48, totaling almost R2 billion spent on the disease during the study period. CONCLUSION: The data analyzed demonstrate that, in Brazil, gallbladder diseases represent a significant problem due to the large number of annual hospitalizations and the significant financial impact on the Federal Government.